Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

Re-routing Metabolism by the Mitochondrial Pyruvate Carrier Inhibitor MSDC-0160 Attenuates Neurodegeneration in a Rat Model of Parkinson’s Disease - David Mallet; Raphael Goutaudier; Emmanuel L. Barbier; Sebastien Carnicella; Jerry R. Colca; Florence Fauvelle; Sabrina Boulet (Molecular Neurobiology, 2022)